THE PRODUCTION OF KNOWLEDGE IN EDUCATIONAL POLICIES OF PROGRAMS POST GRADUATE IN EDUCATION THE UNIVERSITY STATE PAULISTA - Souza, Kellcia Rezende [UNESP]; Micely Kerbauy, Maria Teresa [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This study examines the underlying trends research on educational policies in the production of graduate programs in Education at the Universidade Estadual Paulista (UNESP). To this end, a bibliographical research with qualitative approach was carried out. Data were analyzed from the abstracts content. We take as an object to understand this issue the dissertations and theses with theme focused on the area of educational policy. 85 studies were selected, from 2009 to 2013. The works reflect the view of prevailing trends and looks in the field of educational policies of the institution's programs, represented under 5 themes: Studies on government policies and programs; Legislation and the right to education; Financing policies and management; Assessment policies and role of political parties and other civil society organizations. The analysis undertaken shows the progress of the focused field of knowledge and the boundaries that appear to consolidate the area.
Keywords: Research; Educational policy; Postgraduate studies